THE MODEL DEVELOPMENT ON LIFE SKILL FASHION IN EMPOWERING LEARNING PARTICIPANTS TO REACH THE SELF RELIANT ENTREPREUNEURSHIP - Maeliah, Mally (International Journal of Education, 2010)
The objective of this study is to develop a model of fashion life skill instruction in empowering learners to reach a self reliant entrepreneurship. Research and development method through seven steps of research was used. The seven steps consisted of empiric (field), Literature review, conceptual model arrangement, model verification, model experiment (implementation), analysis and model revision, and final model. The study was conducted at PKBM (community learning center/CLCs) in Bandung regency. Research subjects were learners of CLCs who chose field of dress making, where learners of Jayagiri CLC were the control group and those of Gegersunten were experiment one. Results of study showed that the model of life skill instruction in the field of dress making in Community Learning Center proved effective in improving learners’ ability to achieve entrepreneurship independence.